2015
DOI: 10.1111/myc.12301
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Arthroderma vanbreuseghemii dermatophytosis at a veterinary school associated with an infected horse

Abstract: We report a case of an outbreak of inflammatory dermatophytoses caused by Arthroderma vanbreuseghemii (formally Trichophyton mentagrophytes pro parte) that involved an infected horse, the owner and at least 20 students, staff and stablemen at a veterinary school in Bern (Switzerland) that presented highly inflammatory dermatitis of the body and the face. Transmission from human to human was also recorded as one patient was the partner of an infected person. Both the phenotypic characteristics and ITS sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Chollet et al [ 60 ] convincingly showed that the original case of C. Robin concerned a human tinea barbae, a disorder generally ascribed to zoophilic species. Isolates of this species show some ITS diversity but are either from animals or from patients with inflammatory dermatophytoses indicating an animal origin; reservoirs are hunting cats, dogs [ 52 ], mice [ 19 ] and horses [ 61 ]. Isolates are able to mate with Arthroderma strains [ 50 ].…”
Section: Nomenclaturementioning
confidence: 99%
“…Chollet et al [ 60 ] convincingly showed that the original case of C. Robin concerned a human tinea barbae, a disorder generally ascribed to zoophilic species. Isolates of this species show some ITS diversity but are either from animals or from patients with inflammatory dermatophytoses indicating an animal origin; reservoirs are hunting cats, dogs [ 52 ], mice [ 19 ] and horses [ 61 ]. Isolates are able to mate with Arthroderma strains [ 50 ].…”
Section: Nomenclaturementioning
confidence: 99%
“…Similarly, dermatophytosis and other fungal infections were the main self-reported zoonoses by veterinary students of the Veterinary Faculty of the University of Utrecht, with a total of 94 cases among the 960 students surveyed [38]. Nevertheless, in the present systematic review only 2 articles reporting dermathomycosis in veterinary students were found, suggesting that the only published cases of fungal infections are those which are etiological, epidemiological or clinical exceptions [69, 70]. …”
Section: Discussionmentioning
confidence: 84%
“…Concerning the animal species associated to infections by Poxviridae virus, ruminants were considered the main source of these agents [61–63], though one student became infected with Orthopoxvirus after being scratched by a cat [64]. Two of the articles that report cases of psittacosis associate this disease to the exposure to birds [33, 34], whereas student’s cases of dermatophytosis were related to contact with cats [69] and an infected horse [70]. In the studies which report the animal species involved in each zoonosis, transmission through direct contact prevails, although indirect infection through contaminated equipment is also described for cryptosporidiosis [50] and dermathopytosis [69].…”
Section: Resultsmentioning
confidence: 99%
“…The ITS sequence of the present isolates was 100% identical to the ITS sequence of various strains isolated worldwide from humans and rabbits, and also once from guinea pig, dog and pig (Table ). It differed by three base pairs of the ITS sequence () of T. mentagrophytes strains that were very frequently isolated from hunting cats, dogs and recently from a horse, and that also cause inflammatory dermatophytoses in humans . Isolates of T. mentagrophytes show some ITS diversity, but are still able to mate with Arthroderma vanbreuseghemii reference strains (Table ,).…”
Section: Resultsmentioning
confidence: 99%
“…It differed by three base pairs of the ITS sequence (AF506034) of T. mentagrophytes strains that were very frequently isolated from hunting cats, dogs and recently from a horse, and that also cause inflammatory dermatophytoses in humans. 16,17 Isolates of T. mentagrophytes show some ITS diversity, but are still able to mate with Arthroderma vanbreuseghemii reference strains ( Table 1, 11 ). The molecular identification of more isolates from rabbits of different origin would be of interest to confirm that a particular T. mentagrophytes genotype with an ITS sequence identical to GU646874 is prevalent in this animal.…”
Section: Resultsmentioning
confidence: 99%